The Existence of the National Social Security System as a Form of Fulfillment of Welfare to the Constitutional Rights of the Community - Lo, Edmund; Rahmadhano, Ibrahagi; Chiesa, Davina; Saly, Jeane Neltje (CV. Rayyan Dwi Bharata, 2023)
At this time the Social Security System is expected to make a positive contribution to improving people's rights. Therefore, the community is expected to be actively involved in development activities, especially in social security. The contents of this journal aim to recommend efforts that can be made to maximize the existence of improving the community's economy, analyzing social changes that occur in society. And provide information regarding factual conditions of activities in the form of fulfillment of welfare and steps that can be taken to encourage improvement.